Dimensioning and tolerancing method for product design and process planning - Ong, Chee Teck. (2009)
The assignment of dimensions and tolerances in product design and process planning is often one of the primary and most important tasks of an engineer. Although the mechanics of component and process dimensioning and tolerancing are interlinked, the tasks and roles of the design and manufacturing engineers are often executed independently, with minimum or no communication between them.